Arrhenoseius Walter & Lindquist (Mesostigmata: Blattisociidae): newly recorded from the Oriental Realm with description of two new species from China. Issue 7 (2nd October 2020) - Yun, Long; Yi, Tian-Ci; Jin, Dao-Chao; Guo, Jian-Jun
ABSTRACT: The genus Arrhenoseius Walter & Lindquist, 2000 is recorded for the first time from the Oriental Realm on the basis of two new species. Arrhenoseius hallidayi sp. nov . can be distinguished from other species of the genus by the ventrianal shield bearing five pairs of ventral setae and unsclerotised ventro-lateral cuticle without setae in the adult female, and Arrhenoseius granulatus sp. nov . can be distinguished by the ventrianal shield bearing eight pairs of ventral setae and unsclerotised lateral cuticle with six pairs of setae. A key to species of Arrhenoseius is given based on the adult females. http://www.zoobank.org/urn:lsid:zoobank.org:pub:086088AD-68A2-4464-BF8E-F113E5721FD0